Penguatan Nilai-Nilai Kewarganegaraan Digital Melalui Pembelajaran PPKn Berbasis Teknologi di Sekolah Dasar - Nugroho, Feby Arief; Wijayati, Ida Wahyu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Digital transformation in education demands the reinforcement of character values, including digital citizenship, from the early stages of schooling. This study aims to analyze how Civic and Pancasila Education (PPKn) can serve as a medium to strengthen digital citizenship values through the use of technology. The method used is qualitative with data collection techniques through observation, teacher interviews, and documentation of learning activities in two elementary schools in Magetan Regency. The resulting data were analyzed descriptively. The findings indicate that PPKn teachers are able to utilize interactive digital media such as Canva, Padlet, and Google Classroom to instill values of integrity, digital responsibility, and media ethics. However, challenges remain in terms of digital literacy and limited access to devices, which can be addressed through teacher training and school policy support. This study recommends strengthening teachers' digital pedagogical capacity and systematically integrating digital citizenship values into the curriculum.